2009
DOI: 10.1097/mcp.0b013e32832d0403
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in sarcoidosis: a systematic review

Abstract: This review illustrates the importance of fatigue as an under-recognized complication of sarcoidosis. It further emphasizes the need for longitudinal prospective studies to better define sarcoidosis fatigue, explore its impact on quality of life, define aggravating or alleviating factors and evaluate new potential treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 30 publications
4
62
0
2
Order By: Relevance
“…They were: for FEF 25 No correlation between 6-minute walking distance and FAS score was found either (r = 0.01, p = 0.9) (Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were: for FEF 25 No correlation between 6-minute walking distance and FAS score was found either (r = 0.01, p = 0.9) (Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
“…The strength of the quadriceps muscle of the thigh, of the palm muscles, and respiratory muscles was significantly lower in sarcoidosis compared to the control group. A correlation between muscle strength and fatigue was found to be weak in men and strong in the examined women [25]. The research conducted by Spruit showed that that patients complaining of fatigue had lower muscle mass and lower exercise tolerance, compared to healthy subjects [11].…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is an important aspect of sarcoidosis. There have been an increasing number of studies regarding sarcoidosis associated fatigue [63]. There was a correlation between fatigue and 6MWD [45].…”
Section: Quality Of Lifementioning
confidence: 99%
“…22,24 Initially developed by De Vries et al, 25 it is a well-validated and reliable scale. 22 The questionnaire consists of 2 subscales, 5 questions each on the physical and mental aspect of fatigue. There are 5 answer options ranging from "never" to "always."…”
Section: Fasmentioning
confidence: 99%
“…21 Although there are several studies examining specific putative reasons for elevated fatigue levels in sarcoidosis, many of them are based on relative small sample sizes. 22 Furthermore, the association between comorbidity and fatigue has been mentioned only in case reports. 23 Hence, in the current study, we intended to comprehensively test several factors associated with fatigue in sarcoidosis.…”
Section: Introductionmentioning
confidence: 99%